Secure Surveillance System Using Chaotic Image Encryption Technique. Issue 1 (December 2020) - Ghosh, Gopal; Kavita,; Verma, Sahil; Jhanjhi, NZ; Talib, M N
Abstract: In the current data transmission situation, digital images constitute a large part of visual communication. Their security is thus an essential field of concern. This paper analyses several chaotic maps for the encryption of images and discusses their advantages and disadvantages. The characteristics of chaotic maps such as stochastic, ergodicity and highly sensitive initial conditions allow them reliable to encrypt images. Many of the previously proposed imaging approaches used chaotic, low-dimensional charts that display the lowest security and have very less potential to handle force and attacks. To solve this challenge, scientists have proposed multiple broad chaotic charts. In this paper the characteristics and techniques of some chaotic maps used to encrypt images were reviewed. Also for images like boat, airplane, peppers, lake, house chaotic encryption is applied and analysed.